Elaboration of Pharmacopoeial Quality Standards for Bacteriophage Products - T. M. Kargina; E. I. Sakanyan; D. S. Davydov; R. L. Parfenyuk (Биопрепараты: Профилактика, диагностика, лечение)
Bacteriophages are novel safe and efficacious medicinal products that are used for treatment of intestinal infections and purulent inflammations. The fact that virulent phages can be adapted to fight antibiotic-resistant bacterial strains makes this group of medicines a promising means of treatment of infections associated with medical interventions. The elaboration of quality standards for bacteriophage products will enable alignment of the quality requirements and test methods. There are no monographs on bacteriophage products in pharmacopoeias of other countries, therefore, the development of general chapters on groups of test methods used in bacteriophage quality control and monographs on bacteriophages for the State Pharmacopoeia of the Russian Federation (Ph. Rus.) was a very relevant and timely initiative. The aim of the study was to elaborate pharmacopoeial quality standards for bacteriophages approved in the Russian Federation for therapeutic and prophylactic indications. The authors of the study analysed product specification files and master production records for bacteriophages produced in the Russian Federation. They determined common GMP-compliant production steps, the selection criteria for bacteriophage strains and bacteria production strains, and cultivation and storage conditions. The authors standardised bacteriophage quality parameters and brought the test methods in line with the test procedures described in the Ph. Rus., 14th ed. The study summarised test methods used for identification of bacteriophages and determination of their specific activity. The main results of the study were included into the general monograph «Bacteriophages» and individual monographs on bacteriophage products that were included into the current edition of the Ph. Rus. Further studies and elaboration of new quality standards for mono- and multicomponent bacteriophage products, and the use of such products in clinical practice will improve prophylaxis and treatment of various infectious diseases.